2020
DOI: 10.9770/ird.2020.2.1(6)
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of competitiveness of regions of the Republic of Kazakhstan

Abstract: In modern science, there are a large number of techniques focused on the assessment of competitiveness through the analysis of certain resources in the region. However, accounting of human resources in such assessments is not used as a prior factor in identifying regional competitive advantages. Competitive advantages affect not only the efficiency of individual sectors of the economy but also the overall social and economic development of the country. Assessment of the competitiveness of the region should inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Economic freedom significantly affects national competitiveness (Bujancă & Ulman, 2015). Human resources in Kazakhstan present a significant connection to the level of competitiveness (Caurkubule et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Economic freedom significantly affects national competitiveness (Bujancă & Ulman, 2015). Human resources in Kazakhstan present a significant connection to the level of competitiveness (Caurkubule et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In Kazakhstan, a shortage of empirical study is observed, which is the means of assessing the contribution of various measures to the development of corporate innovations, their relationship with competitiveness and productivity, and researching the models of innovative behavior of firms. In this context, notable publications such as (Onyusheva, 2017), (Smirnova, 2016), (Tumalavičius et al, 2017), (Ivanov et al, 2012), (Caurkubule et al, 2020), (Chehabeddine, Tvaronavičienė, 2020), (Vigliarolo, 2020) are to be singled out. There are even fewer works that would systematically examine the impact of public policy on the behavior of business entities at the micro level (Jumakulov et al, 2019), (Musaripov et al, 2019), (Kurmanov et al, 2019), (Popova et al, 2019), (Pukala & Petrova, 2019), (Lazarova et al, 2015), (Yankovyi et al, 2019), (Zbierowski, 2017), (Zahars & Stivrenieks, 2018), (Pachura, 2015), (Lincényi, Čársky, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been widely acknowledged in theory as well as in practice that exportation leads to several economic benefits for a country. Such as income growth, foreign exchange earnings used to finance imported goods and advancement in technology (Verter & Bečvářová, 2016;Eddelani et al, 2019;Caurkubule et al, 2020). Likewise, export commodity by a country represents one of the important sources of foreign income that ease pressure on balance of payments (BOP) and generate employment.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%